Granulomatosis with polyangiitis masquerading as community acquired pneumonia: a case report - Suresh, Surabhi (International Journal of Research in Medical Sciences, 2025)
A 32-year-old female with a known history of hypothyroidism presented with a 10-day history of fever, cough, fatigue, and breathlessness, along with initial symptoms of myalgia and headache. There was no prior history of chronic respiratory illness or tuberculosis exposure. Clinical examination revealed fever, tachypnoea, hypoxia, and pallor, with localized coarse crepitations over the right lung fields. Laboratory evaluation showed anemia, neutrophilic leukocytosis, elevated CRP and ESR, and a negative procalcitonin. COVID-19 rapid antigen test was positive. Chest X-ray revealed right-sided consolidation with bilateral patchy opacities. Despite supportive care and broad-spectrum antibiotics, the patient deteriorated, requiring non-invasive ventilation. Chest CT revealed bilateral subpleural and peribronchial consolidations with cavitation and mediastinal lymphadenopathy. Microbiological workup including blood/sputum cultures and CBNAAT was negative. Bronchoscopy showed mucopurulent secretions, but BAL panel was negative. Autoimmune workup was unremarkable. CT-guided lung biopsy revealed granulomatous inflammation with vasculitis, confirming granulomatosis with polyangiitis (GPA). The patient showed marked clinical and radiological improvement with corticosteroids and Rituximab.